Enhanced sintering behavior of LSGM electrolyte and its performance for solid oxide fuel cells deposited by vacuum cold spray. Issue 15 (December 2017) - Wang, Li-Shuang; Li, Cheng-Xin; Li, Guang-Rong; Yang, Guan-Jun; Zhang, Shan-Lin; Li, Chang-Jiu
Abstract: How to obtain dense La0.8 Sr0.2 Ga0.8 Mg0.2 O3 (LSGM) electrolyte at low sintering temperature (<1300 °C) is a challenge to improve solid oxide fuel cell (SOFC) performance at intermediate operation temperature. In this study, a double-layer design method for vacuum cold spray (VCS) prepared-LSGM electrolyte assisted with two-step sintering at a low temperature was proposed. The sintering behavior of VCS deposited LSGM layers at 1200 °C was investigated. The LSGM layers became denser in most regions except the appearance of some cracks. Subsequently, the effect of a second LSGM layer on the sintered top layer was studied to block cracks. Results showed that the co-sintered layer with a thickness of approximately 5 μm presented a maximum open circuit voltage of ∼0.956 V at 650 °C and a maximum power density of 592 mW/cm 2 at 750 °C. Result indicates that the sintering assisted VCS is a promising method to prepare the LSGM electrolyte applied in intermediate temperature SOFCs.